Kinematics at Singular Sets - Steinmann, Paul (Spatial and Material Forces in Nonlinear Continuum Mechanics, 2022)
This chapter revisits the relevant continuum kinematics at singular sets, i.e. at singular surfaces and at singular curves and points, thereby elaborating on the jumps in the nonlinear deformation maps and their associated tangent, cotangent, and measure maps.
CRIS-Team Scopus Importer:2022-04-15